Functional neuroanatomy of the cognitive process of mapping during discourse comprehension. - Robertson, David A.; Gernsbacher, Morton Ann; Guidotti, Seline J. (Psychological Science., 2000)
The writers employ functional magnetic resonance imaging (ƒMRI) in order to identify brain regions involved in the process of mapping coherent discourse onto a developing mental representation. They manipulate discourse coherence by presenting sentences with definite articles or indefinite articles. They argue that, compared with reading unrelated sentences, comprehending connected discourse generated more neural activity in the right than in the left hemisphere of the frontal lobe. Therefore, they contend that the right hemisphere of the frontal lobe is involved in some of the processes underlying mapping. In addition, they assert that, in contrast, left-hemisphere structures were associated with lower-level processes in reading. Finally, their findings show the utility of using ƒMRI to examine the neural substrates of higher-level cognitive processes such as discourse comprehension.